Cancer mortality among workers in the German rubber industry: 1981-91. Issue 5 (May 1996) - Weiland, S K; Mundt, K A; Keil, U; Kraemer, B; Birk, T; Person, M; Bucher, A M; Straif, K; Schumann, J; Chambless, L
Abstract : OBJECTIVES: To determine the cancer specific mortality of active and retired workers of the German rubber industry with emphasis on cancer sites which have been associated with the rubber industry in previous studies. METHODS: A cohort of 11, 663 German men was followed up for mortality from 1 January 1981 to 31 December 1991. Cohort members were active (n = 7536) or retired (n = 4127) at the beginning of the study, and had been employed for at least one year in one of five study plants producing types or general rubber goods. Vital status was ascertained for 99.7% of the cohort members, and cause of death found for 96.8% of the 2719 decedents. Age and calendar year adjusted standardised mortality ratios (SMR) and 95% confidence intervals (95% CI) were calculated overall from national reference rates and stratified by year of hire and by years since hire. RESULTS: Mortalities from all causes (SMR 108; 95% CI 104-112) and all cancers (SMR 111; 95% CI 103-119) were significantly increased in the study cohort. Significant excesses in the mortalities from lung cancer (SMR 130; 95% CI 115-147) and pleural cancer (SMR 401; 95% CI 234-642) were identified. SMRs higher than 100 were found for cancers of the pharynx (SMR 144; 95% CI 76-246), oesophagus (SMR 120; 95% CI 74-183), stomach (SMR 110; 95% CI 86-139), rectum (SMR 123; 95% CI 86-170), larynx (SMR 129; 95% CI 69-221), prostate (SMR 108; 95% CI 84-136), and bladder (SMR 124; 95% CI 86-172), as well as for leukaemia (SMR 148; 95% CI 99-213). Mortalities from liver cancer, brain cancer, and lymphoma were lower than expected. CONCLUSIONS: Mortalities from cancer of several sites previously associated with the rubber industry were also increased among workers of the German rubber industry. Results of the stratified analyses are consistent with a role of occupational exposure in the aetiology of some of these cancers.